2020
DOI: 10.1016/s2214-109x(19)30482-6
|View full text |Cite|
|
Sign up to set email alerts
|

Estimates of incidence and mortality of cervical cancer in 2018: a worldwide analysis

Abstract: Background The knowledge that persistent human papillomavirus (HPV) infection is the main cause of cervical cancer has resulted in the development of prophylactic vaccines to prevent HPV infection and HPV assays that detect nucleic acids of the virus. WHO has launched a Global Initiative to scale up preventive, screening, and treatment interventions to eliminate cervical cancer as a public health problem during the 21st century. Therefore, our study aimed to assess the existing burden of cervical cancer as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
2,359
1
101

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,808 publications
(2,493 citation statements)
references
References 63 publications
32
2,359
1
101
Order By: Relevance
“…In addition, high LOXL2 expression was significantly correlated with poor OS and DFS in cervical cancer. However, the mortality of cervical cancer is related to age, older women were seen to have the highest mortality rates (36). In our study, we found that high-LOXL2 cluster showed younger mean diagnostic age, while high-LOXL2 cluster showed poor cancer survival, which meant the poor prognosis in high-LOXL2 cluster was not completely on account of age at initial pathological diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, high LOXL2 expression was significantly correlated with poor OS and DFS in cervical cancer. However, the mortality of cervical cancer is related to age, older women were seen to have the highest mortality rates (36). In our study, we found that high-LOXL2 cluster showed younger mean diagnostic age, while high-LOXL2 cluster showed poor cancer survival, which meant the poor prognosis in high-LOXL2 cluster was not completely on account of age at initial pathological diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…According to the World Health Organization (WHO), cervical cancer is the fourth most common cancer in women worldwide, with almost 90% of deaths occurring in low-and middle-income countries (LMICs) [1,2]. In LMICs like India and in sub-Saharan Africa, cervical cancer is the second leading cause of cancer among women and the leading cause of female cancer deaths in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is the second most common cancer in females from low-to-middle-income countries. Around 310,000 deaths occur annually due to cervical cancer [1]. Human papillomavirus (HPV) infection is the major cause of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%